Recovering Sturm-Liouville operators on hedgehog-type graphs with general matching conditions - Freiling, Gerhard; Yurko, Vjacheslav (Eurasian Mathematical Journal, 2014)
We study boundary value problems on hedgehog-type graphs for second-order ordinary differential equations with general matching conditions. We establish properties of spectral characteristics and investigate the inverse spectral problem of recovering the coefficients of a differential equation from the spectral data. For this inverse problem we prove a uniqueness theorem and provide a procedure for constructing its solution.